Effects of exogenous protease supplementation on growth performance, liver health, immunity and intestinal microbiota of grass carp (Ctenopharyngodon idella) - Tingyao Zhu; Lihui Sun; Qian Li; Jianhu Jiang; Haiqi Zhang; Zhangying Ye; Jianming Chen; Jianlin Guo (Aquaculture Reports)
This study aims to investigate the effects of dietary supplementation with protease on the growth performance, liver health, immunity, and intestinal microbiota of grass carp. Three levels of protease, 0 U/kg (P0), 6000 U/kg (P6000) and 12,000 U/kg (P12000), were formulated into diets using post-spray technology. After 9 weeks of feeding, the P6000 group had a higher weight gain rate than the P0 group, with both P6000 and P12000 groups exhibiting higher protein retention ratio and lower feed conversion ratio compared to P0. As protease levels increased, crude protein content and intestinal protease activity increased, while alkaline phosphatase (ALP) content decreased. Concurrently, the P6000 group showed higher aspartate transaminase (AST) and triglyceride (TG) levels but lower amylase content compared to P0. In terms of immune indicators, the expression levels of Intelectin and MHC-II β in the P6000 and P12000 groups were significantly lower than in P0, and IgM expression gradually increased with increasing protease levels. After challenge with Aeromonas veronii, the P12000 group showed higher survival rate. The histological results indicated that the intestinal villi length in the P6000 group was notably longer than in other groups. The intestinal microbiota analysis revealed that with increasing protease levels, Fusobacteriota abundance decreased and Actinobacteriota and Cyanobacteria abundance increased at the phylum level, while Aeromonas relative abundance decreased at the genus level. Overall, 6000 U/kg protease boosts grass carp growth and nutrient retention maximally, while 12,000 U/kg protease increases survival but may increase liver metabolic burden. Given these outcomes, the optimal protease inclusion level for grass carp aquaculture is approximately 6000 U/kg.